2011
DOI: 10.7150/thno/v01p0322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 111In-Labeled Cyclic RGD Peptides: Effects of Peptide and Linker Multiplicity on Their Tumor Uptake, Excretion Kinetics and Metabolic Stability

Abstract: Purpose: The purpose of this study was to demonstrate the valence of cyclic RGD peptides, P-RGD (PEG4-c(RGDfK): PEG4 = 15-amino-4,710,13-tetraoxapentadecanoic acid), P-RGD2 (PEG4-E[c(RGDfK)]2, 2P-RGD4 (E{PEG4-E[c(RGDfK)]2}2, 2P4G-RGD4 (E{PEG4-E[G3-c(RGDfK)]2}2: G3 = Gly-Gly-Gly) and 6P-RGD4 (E{PEG4-E[PEG4-c(RGDfK)]2}2) in binding to integrin αvβ3, and to assess the impact of peptide and linker multiplicity on biodistribution properties, excretion kinetics and metabolic stability of their corresponding 111In ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 44 publications
13
69
0
Order By: Relevance
“…6466 The integrin α v β 3 /α v β 5 binding affinity followed a general trend: FITC-3P-RGD 2 ∼ FITC-Galacto-RGD 2 > FITC-RGD 2 ≫ c(RGDfK) > FITC-3P-RGK 2 , which was consistent with the results for their DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracetic acid) and HYNIC (6-(2-(2-sulfonatobenzaldehyde)hydrazono)nicotinyl) derivatives. 44,6071 The lower binding affinity of FITC-3P-RGK 2 (IC 50 = 589 ± 73 nM) than that of FITC-3P-RGD 2 (IC 50 = 32 ± 7 nM) clearly demonstrated the RGD-specificity of the FITC-conjugated cyclic RGD peptides.…”
Section: Resultsmentioning
confidence: 97%
“…6466 The integrin α v β 3 /α v β 5 binding affinity followed a general trend: FITC-3P-RGD 2 ∼ FITC-Galacto-RGD 2 > FITC-RGD 2 ≫ c(RGDfK) > FITC-3P-RGK 2 , which was consistent with the results for their DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetracetic acid) and HYNIC (6-(2-(2-sulfonatobenzaldehyde)hydrazono)nicotinyl) derivatives. 44,6071 The lower binding affinity of FITC-3P-RGK 2 (IC 50 = 589 ± 73 nM) than that of FITC-3P-RGD 2 (IC 50 = 32 ± 7 nM) clearly demonstrated the RGD-specificity of the FITC-conjugated cyclic RGD peptides.…”
Section: Resultsmentioning
confidence: 97%
“…The fact that the tumor uptake of 99m Tc-3G-RGD 2 and 99m Tc-3P-RGD 2 is well-comparable to that of 99m Tc-RGD 4 (Figure 7) within experimental errors suggests that multimeric cyclic RGD peptides are not necessarily multivalent in binding to integrins, and the contribution from the concentration factor is not as much as that from the bivalency factor. 39,41 In addition, the capability of a multimeric cyclic RGD peptide to achieve bivalency also depends on the α v β 3 density in tumor tissues. If the tumor α v β 3 density is high, the distance between two neighboring α v β 3 sites will be short.…”
Section: Maximizing Binding Affinity Via Multimerizationmentioning
confidence: 99%
“…39,41,42 It was found that the glioma uptake (% ID/g at < 24 h p.i.) follow the general ranking order of 111 In-6G-RGD 4 ~ 111 In-6P-RGD 4 ~ 111 In-3P-RGD 2 ≫ 111 In-P-RGD 2 > 111 In-P-RGD (Figure 9).…”
Section: Maximizing Binding Affinity Via Multimerizationmentioning
confidence: 99%
“…7,[16][17][18][19][32][33][34][35][36][37][38][39][40][41][42] This trend is observed from derivatives having monomer-to-tetramer RGD derivatives. [16][17][18][19]32,33,[36][37][38][40][41][42] However, a steady increase of uptake in other nontarget organs, for example, the liver, intestine, and kidneys, is also reported as the number of RGD molecule increase. A comparison of biological behavior of radiolabeled RGD monomer, dimer, and tetramer revealed that dimers exhibit rapid tumor localization and significant tumor retention with excellent target/nontarget ratios and is the most suitable candidate for tumor imaging.…”
Section: Introductionmentioning
confidence: 90%